Consensus guidelines for the investigation and management of encephalitis in adults and children in Australia and New Zealand. Issue 5 (May 2015) - Britton, P. N.; Eastwood, K.; Paterson, B.; Durrheim, D. N.; Dale, R. C.; Cheng, A. C.; Kenedi, C.; Brew, B. J.; Burrow, J.; Nagree, Y.; Leman, P.; Smith, D. W.; et al.
Abstract Encephalitis is a complex neurological syndrome caused by inflammation of the brain parenchyma. The management of encephalitis is challenging because: the differential diagnosis of encephalopathy is broad; there is often rapid disease progression; it often requires intensive supportive management; and there are many aetiologic agents for which there is no definitive treatment. Patients with possible meningoencephalitis are often encountered in the emergency care environment where clinicians must consider differential diagnoses, perform appropriate investigations and initiate empiric antimicrobials. For patients who require admission to hospital and in whom encephalitis is likely, a staged approach to investigation and management is preferred with the potential involvement of multiple medical specialties. Key considerations in the investigation and management of patients with encephalitis addressed in this guideline include: Which first‐line investigations should be performed?; Which aetiologies should be considered possible based on clinical features, risk factors and radiological features?; What tests should be arranged in order to diagnose the common causes of encephalitis?; When to consider empiric antimicrobials and immune modulatory therapies?; and What is the role of brain biopsy?